Influencia del agregado reciclado en la resistencia a la compresión y el porcentaje de absorción de adoquines peatonales Lima 2020 - Aguilar Cipriano, Jhan Carlos (2021)
A systematic review is carried out to determine the influence of recycled aggregate on the properties of concrete designed for pedestrian pavers, selecting highly relevant investigations, filtering them by years, focus and results. Which contribute to make a comparison of results in the properties of resistance to compression and percentage of absorption of pavers subjected to different percentages of replacement of recycled aggregate in its structure, in order to determine the influence, they have on said properties. Through the analysis and synthesis of results, the influence of the recycled aggregate is validated, affecting the decrease in its resistance to compression and the increase in the percentage of absorption. However, taking into account the information presented and based on the statistics, it is valid to conclude that by replacing up to 25% of the coarse aggregate with recycled aggregate, an adequate mixture can be achieved, complying with the parameters estimated by NTP. 399,611 according to their properties. Likewise, it is valid to mention that, at a higher percentage of replacement, the properties vary unfavorably